Involvement of Student Through the MBKM Program to Create a Law-Conscious Village - Serah, Yenny Aman; Setiawati, Rini; Sebayang, Aleksander; ., Siswadi; Nugraha, Adhytia; Mutiara Sirait, Resmaya Agnesia (KnE Social Sciences, 2023)
The development of legal awareness is a critical social issue currently receiving government attention and being promoted through various development efforts. To foster public legal awareness, the Legal Awareness Village (DSH) program has been launched and implemented. However, in West Kalimantan, out of 2,076 villages/kelurahan, only 231 have been designated as legally assisted villages by the West Kalimantan Governor’s Decree as of 2021. Moreover, only 166 villages/kelurahan have received the Anubawa Sasana Desa award from the Ministry of Law and Human Rights as Legal Awareness Villages. This study aims to explore how students can play a role in realizing the fulfillment of village awareness indicators to increase community legal awareness. The research employs socio-legal research methods with a qualitative approach, using questionnaires, interviews, and focused discussions with stakeholders for data collection. The study findings indicate that the knowledge and understanding of the community in fulfilling the achievement indicators of law-aware villages, consisting of various legal dimensions, are still lacking. As a solution, researchers propose involving students as campus personnel who can assist villages in becoming law-conscious communities. This strategic effort can be achieved through synergy between the Legal Awareness Village program from the Ministry of Law and Human Rights, and the Independent Campus Learning Program Merdeka (MBKM) from the Ministry of Education and Culture, in collaboration with the Regional Government. Keywords: community legal awareness, law aware village, free learning, student